Multivariate statistical analysis of cold season wheat yield under drought conditions Alireza Razavi - Razavi, Alireza (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
Effect of drought stress on cold season wheat varieties investigated at Jolgeh-rokh station of Torbat Heydarieh agricultural and resources research center during 2012 and 2013. The experiment contained 18 inbred lines and promised varieties studied in optimal and limited irrigation levels. Two separate complete randomized block designs with three replications were carried out. At limited irrigation level plants did not irrigated at dough stage and physiological maturity stage. Measured treats was: plant height, spike length, peduncle length, grains/spike, grain weight, thousand grain weight, spike weight, harvest index, grain and biological yield. Results showed that Cold wheat 14 was the best variety in both irrigation levels. Grain yield significantly correlated with grain yield and biological yield at optimal condition. There was a positive correlation between biological yield peduncle weight and harvest index with grain yield at drought condition. Stepwise regression analysis showed that yield variation control by thousand grain weight, grains/spike and spike weight at optimal irrigation condition. Peduncle length was the only variable enters to regression model at drought condition. Peduncle length and weight had the highest indirect effect on yield as shown by path analysis. Factor analysis indicated that three factors accounted for about 80 percent of the total variation among characters. Investigating the drought susceptibility indices showed that mean productivity index and stress susceptibility index was the best in selecting tolerate varieties.